The Effect of Archaebacteria and Eubacteria Web-Based Learning Media on Students’ Cognitive Learning Outcomes in Balikpapan - Hidayah, Maulida Ulfa; Agil, Muhamad; Lumowa, Sonja V. T.; Boleng, Didimus Tanah; Lestari, Rini Eka (Universitas Sembilanbelas November Kolaka, 2024)
Cognitive learning outcomes are an aspect related to the reasoning or thinking process, namely the ability and activity of the brain to develop rational abilities. Based on observation of schools in Balikpapan, students’ cognitive learning outcomes still have not achieved the minimum completion criteria (KKM). Students have difficulties in learning archaebacteria and eubacteria because the concepts are abstract. The lack of variations in learning media has made this topic more difficult to teach. This research aimed to determine the influence of Archaebacteria and Eubacteria web-based learning media on students’ cognitive learning outcomes in Balikpapan. The type of research was quasi-experimental with a pretest-posttest control group design. The study population was all senior high schools in Balikpapan. The sampling technique used purposive sampling. The samples of this research were three senior high schools in Balikpapan. The subjects of this research were students of SMAN 1 Balikpapan, SMAN 2 Balikpapan, and SMA Patra Dharma Balikpapan. Data analysis technique using ANCOVA (SPSS Statistics 23). According to the research findings, the average cognitive learning score of the cognitive learning score test in the experimental class is higher than the control class, which is 72.98 67.84. The prerequisite test shows that data were normally distributed and class groups derived from a homogenous population. The hypothesis test using ANCOVA at a 0.05 significance level shows that there is an effect of applying web-based learning media on students’ cognitive learning outcomes in learning archaebacteria and eubacteria.